Simple Multi Attribute Rating Technique untuk Pendukung Keputusan Pemberian Sanksi Siswa - Gaja, Rizqi Nusabbih Hidayatullah; Defit, Sarjon; Nurcahyo, Gunadi Widi (Jurnal KomtekInfo, 2024)
As one of the schools that advances the courtesy of MAN 1 Padangsidimpuan concludes facing the challenge of monitoring and dealing with student violations effectively and efficiently. In this case, MAN 1 Padangsidimpuan has a student order as a reference to discipline his students. The madrasah seriousness of the need to monitor students in committing violations is very low and is still undigitalized. The research aims to design an application that can monitor student violations and support decisions to sanction students who violate order. The method used in this research is the Simple Multi Attribute Rating Technique (SMART). This method has five stages, namely, determining the number of criteria, giving weight to each criterion, normalizing the value of the criterions, giving value to each alternative, and calculating the final value. The data set processed in this study comes from the student problem book in MAN 1 Summary of the 2023/2024 school year. The dataset consists of 147 student violations records. The data sets will be tested calculations manually with calculations using the application. The results of this study show that the application can record student violations well. The result of manual calculations with the calculations on the application has similar results. From the calculation results, the highest final score a student gets is 24 points. The sanctions are given according to the points earned, namely, collecting garbage. Therefore, this research can help Teacher Counseling in monitoring student violations and make the reporting process to the Chief Madrasah faster and more accurate. Applications only help make decisions by providing information or alternative solutions to existing problems. The final decision remains with the decision maker.